2005
DOI: 10.1007/s11191-004-1791-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics as the Logical Point of Entry for the Enculturation into Scientific Thinking

Abstract: Force in modern classical mechanics is unique, both in terms of its logical character and the conceptual difficulties it causes. Force is well defined by a set of axioms that not only structures mechanics but science in general. Force is also the dominant theme in the 'misconceptions' literature and many philosophers and physicists alike have expressed puzzlement as to its nature. The central point of this article is that if we taught mechanics as the forum to discuss the nature of mechanics itself, then we wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Students often experience difficulties when solving problems related to the dynamics of motion. Some students have difficulty in solving problems related to force (Carson & Rowlands, 2005;Matthews, 2009;Rowlands, Graham, Berry, & McWilliam, 2007) and the concept of acceleration (Coelho, 2010;Tasar, 2010). The results of the study by (Narjaikaew, 2013) showed that some students did not understand the concept of motion and force.…”
Section: Introductionmentioning
confidence: 99%
“…Students often experience difficulties when solving problems related to the dynamics of motion. Some students have difficulty in solving problems related to force (Carson & Rowlands, 2005;Matthews, 2009;Rowlands, Graham, Berry, & McWilliam, 2007) and the concept of acceleration (Coelho, 2010;Tasar, 2010). The results of the study by (Narjaikaew, 2013) showed that some students did not understand the concept of motion and force.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the construction of a conceptual understanding of a subject domain, as opposed to the memorisation of rule-of-thumb procedures, manifests the conditions for development towards creativity. For example, the pupil in mechanics who changes her conception of force and motion from what may be described as an Aristotelian notion to a Newtonian one manifests creativity (see Carson & Rowlands, 2005). To think of problems concerning force and motion within possible world contexts of frictionless surfaces or where gravity can be an option, without resorting to casting the problem algebraically, is to think in a creative context.…”
Section: Creativity and The Subject Mattermentioning
confidence: 99%
“…or 'Gravity is switched off and I throw a ball in the air. Describe its motion' (see Carson & Rowlands, 2005), has created the conditions for creative development whereby the class uses its imagination but is constrained to think within the domain of the subject. This is elaborated further in the section after next.…”
Section: Creativity and The Subject Mattermentioning
confidence: 99%
See 2 more Smart Citations